STRATEGI PEMASARAN YANG DILAKUKAN “RESTAURANT BLACK CANYON COFFEE” DI PLAZA TUNJUNGAN III SURABAYA DALAM MEMASARKAN PRODUKNYA - Dheenaz Malvinas Ticha (Fakultas Ekonomi Universitas 45 Surabaya, 2014)
To winning the competition, the factors of customer satisfaction are very important things, because of that, the marketers are always expected to hold a renewal and introduction of products to the consumer who wants to be reached to retain the customers. Black Canyon Coffee restaurants and also a coffee shop of franchise concept from Thailand that located at Tunjungan Plaza 3 floors 4 and at Surabaya Town Square also have to do a marketing strategy to marketing their products. The conclusion of this research, consumers of Black Canyon Coffee restaurants are: (1) men who aged of 21-35 years; (2) consumers that obtain information from the friend by 47%, 37% are from the business relationship, 13% are from the family; (3) consumers desires to come again to the Black Canyon Coffee restaurant as much as 44% are said maybe, and 37% are said yes. The marketing strategy that undertaken by Black Canyon Coffee restaurant is to increasing presentation speed and food quality, increasing cleanliness of restaurant, hospitality and neatness of staffs’ appearance. The increasing of promotion both through of printing and electronic media, or by a billboard so that its presences are more to be known by the public.